НЕДОСТАТОЧНОСТЬ ВИТАМИНА D И СОСТОЯНИЕ ТКАНЕЙ ПОЛОСТИ РТА (World Science, 2020)
Currently, regardless of the age and social affiliation of the population, periodontal disease is the most common. Despite the modern technologies used in dentistry, the issues of prevention and treatment in dentistry remain unresolved. Dentists are interested in the fact that periodontal diseases are inextricably linked with systemic disorders in the body, which are responsible for its physiological functions. And the effectiveness of treatment for periodontal diseases is affected by all the factors that lead to the pathological process, i.e. diseases of internal organs and periodontal diseases are inextricably linked. In this regard, the metabolism in the body of certain vitamins, in particular vitamin D, forces dentists to re-examine the effect of these vitamins on pathological factors that lead to pathologies of the oral cavity.Diseases that affect the duration and quality of life of the patient have the ability to spread widely, for example, cardiovascular diseases, tuberculosis, HIV infection, etc., and oral diseases, in particular, caries and pathologies, can be attributed to this category. periodontium.